Students’ Progress in Writing a Recount Genre; A Case Study at One of Junior High Schools in Tembilahan, Riau Province - Rahmatunnisa, Rahmatunnisa; Putra, Edi Susrianto Indra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The Competence-Based Curriculum stated that the students must be able to communicate in English with each other, both in spoken and written languages by using appropriate variety of languages within transactional and monolog discourse, including Narrative, Recount, Descriptive, Report, and Anecdote. This study tried to explore the students’ progress in writing a Recount genre and what teaching and learning activities in which might lead to students’ progress. The present study was largely qualitative. The participants of the study were the eighth grade students and one teacher at one junior high school in Tembilahan, Riau Province. In order to gain valid data the study employed triangulation of data collection method in terms of students’ texts, classroom observation, and interview. The data were analyzed qualitatively with the help of some quantitative calculation. First, data from students’ texts were analyzed qualitatively to identify the schematic structure and thematic structure, and they were also analyzed quantitatively in terms of frequency and percentage to identify the tendency of linguistic feature occurrences. Second, data from classroom observation and interview were analyzed qualitatively. Next, data from observation were summarized and classified, and data from interview were transcribed and classified according the research questions. Finally data from the three sources were synthesized to answer the research questions. It is found that the students showed progress in writing a Recount genre. Data from the analysis of students’ writing showed that the students were able to create a Recount text with appropriate schematic structure and linguistic features. Additionally, they also applied good thematic structure in joint construction text and final text. Data from classroom observation showed that the students improved their attitude in writing activities from the first meeting to the sixth one. Data from interview with the teacher also showed that the students made meaningful progress in which they made fewer mistakes in grammar and punctuation. The teacher also said that the students used more appropriate English expressions. The findings of the study also reveal that the teacher employed genre based approach which involved: BKOF, MOT, JCOT, and ICOT stages. And the teaching and learning activities which lead to the students’ progress in writing Recount genre are the activities in BKOF, MOT, and JCOT. The results of this study are expected to provide information on the actual condition of teaching and learning activities in writing a Recount genre. They may also become useful sources for English teacher to investigate students’ progress and to provide informative input for other researchers who intend to conduct research in the same field with certain interest.